A new fossil soldier beetle (Coleoptera, Cantharidae, Silinae) from Eocene Baltic amber - Fanti, Fabrizio; Pankowski, Michael J. (Zootaxa, 2018)
A new genus and species of fossil soldier beetle Markus karenae gen. et sp. nov. is described and illustrated from Eocene Baltic amber. Its morphological characteristics place it in the taxonomic position of the subfamily Silinae. It is characterized by a particular lateral pronotal shape with two difform processes, pronotum slightly longer than wide, with a blunt and evident angle near the basal angles, anterior and posterior margins flat and with shallow punctation, and lateral margin strongly granulose and in relief. Furthermore, each of its legs has a claw with one acute tooth at the base, except for the posterior legs where the tooth appears to be blunt. The new taxon is morphologically compared with the other fossil representatives of Silinae from Baltic amber, and with extant Palearctic genera.